Convergence Analysis of Spectral Methods for Integro-Differential Equations with Vanishing Proportional Delays (Journal of Computational Mathematics, 2018)
We describe the application of the spectral method to delay integro-differential equations with proportional delays. It is shown that the resulting numerical solutions exhibit the spectral convergence order. Extensions to equations with more general (nonlinear) vanishing delays are also discussed.
Keywords: Delay integro-differential equations; Proportional delays; Spectral methods; Convergence analysis.